Penerapan Manajemen Keuangan, Humas, Ketatalaksanaan dan Layanan Khusus di Lembaga Pendidikan - Gustina, Nadia; Yuliani, Tri (Indo-MathEdu Intellectuals Journal, 2025)
This article aims to explain the application of management in the education sector, with an emphasis on the components and scope of school administration work. The data sources consist of articles published in academic journals discussing recent research related to educational management, human resource management, financial management, and the implementation of educational policies, as well as books written by experts in the fields of educational management and school administration. The data collection technique includes gathering scientific articles and searching for information through online databases such as Google Scholar, JSTOR, or official sites providing access to research articles, educational policy reports, and relevant publications. The main components in the study of school management include finance, public relations, administration, and special services for schools, as found through literature research. During the implementation phase, these components are interconnected. Furthermore, educational administration responsibilities at the school level include three main components of educational management: the governance foundation of education involving students, teachers, and curriculum, supported by five other elements is organization, finance, facilities and infrastructure, government, and public relations